(untitled) (Global Journal of Human-Social Science, 2016)
The scientific evidence of climate change as a result of greenhouse gas emissions which causes ozone layer depletion is becoming increasingly obvious and clear. Findings revealed that energy from the fossil fuel is the major source of greenhouse emission which destroys the environment and makes it unhealthy for living beings. In Nigeria, conventional energy (oil and gas) with gas flaring has the highest percentage of 52% and liquid fuel of 32% of carbon dioxide (CO 2 ) respectively. This sector contributes revenue of over 70% to Nigeria’s economy and generates an average total 21.8% of greenhouse gas emission. In Nigeria, there is a much more potential for share renewables with 15.4% of total energy production and 8.6 % of energy consumption. In reality with global environmental concern, Nigeria’s carbon dioxide emissions have increased with energy production and consumption. The Integrated Renewable Energy Master Plan of 2008 projects a 26.7% renewable energy contribution to the Nigeria’s energy use and this is expected to reduce CO 2 and greenhouse gas emissions at 38% by 2025.